Estimating the incidence of coeliac disease with capture-recapture methods within four geographic areas in Italy. Issue 3 (June 1996) - Corrao, G; Usai, P; Galatola, G; Ansaldi, N; Meini, A; Pelli, M A; Castellucci, G; Corazza, G R
Abstract : STUDY OBJECTIVE: To estimate the incidence rate of newly diagnosed cases of coeliac disease in Italy. DESIGN: This was a descriptive study of coeliac disease incidence in the period 1990-91. SETTING: During 1990-91 newly diagnosed cases of coeliac disease were signalled by several sources including diagnostic records of departments of paediatrics, general medicine and gastroenterology, national health service records for the supply of gluten free diets and the archives of the Italian Coeliac Society. PATIENTS: Altogether 1475 cases were flagged throughout Italy, 478 of whom were selected, corresponding to 270 individual patients from a target population resident in four areas: Provices of Turin and Cuneo (Piedmont Region, northern Italy); Province of Brescia (Lombardia Region, northern Italy); Umbria Region (central Italy) and Sardinia Region (insular Italy). Only for these areas were patients flagged from several sources and the reference population was identifiable. MAIN RESULTS: The overall crude incidence rates for all ages per 100, 000 residents per year were 2.4, 2.7, 1.5, and 1.7 in the four areas, respectively. The childhood cumulative incidence rates (aged < or = 15 years) per 100, 000 live births were 143, 141, 72, and 80 respectively. The mean ages at diagnosis were similar for both childhood and adult cases throughout the areas–these were around 4 and 34 years respectively. For each area, the incidence rate was constantly higher in the main city than elsewhere. Using the capture-recapture method, an estimated completeness of case archives of 0.84 was obtained, whereas this figure was only 0.47 for hospital sources. CONCLUSIONS: This population based study on the incidence of coeliac disease shows that several information sources should be used to avoid underestimation. The incidence rate of coeliac disease in Italy was among the highest in Europe, and was widely variable showing highest figures in Piedmont and Lombardia and the lowest in Umbria and Sardinia. This trend was not due to different age at diagnosis, which suggests variable diagnostic awareness of the disease rather than different environmental patterns affecting the clinical presentation.